Only the beautiful ebook - Meissner, Susan (2023)
A Best Historical Fiction of Spring Pick by Amazon, PopSugar, AARP, and BookBub! A heartrending story about a young mother’s fight to keep her daughter, and the terrible injustice that tears them apart, by the USA Today bestselling author of The Nature of Fragile Things and The Last Year of the War .   California, 1938— When she loses her parents in an accident, sixteen-year-old Rosanne is taken in by the owners of the vineyard where she has lived her whole life as the vinedresser’s daughter. She moves into Celine and Truman Calvert’s spacious house with a secret, however—Rosie sees colors when she hears sound. She promised her mother she’d never reveal her little-understood ability to anyone, but the weight of her isolation and grief prove too much for her. Driven by her loneliness she not only breaks the vow to her mother, but in a desperate moment lets down her guard and ends up pregnant. Banished by the Calverts, Rosanne believes she is bound for a home for unwed mothers. But she soon finds out she is not going to a home of any kind, but to a place that seeks to forcibly take her baby – and the chance for any future babies – from her. Austria, 1947— After witnessing firsthand Adolf Hitler’s brutal pursuit of hereditary purity—especially with regard to “different children”—Helen Calvert, Truman’s sister, is ready to return to America for good. But when she arrives at her brother’s peaceful vineyard after decades working abroad, she is shocked to learn what really happened nine years earlier to the vinedresser’s daughter, a girl whom Helen had long ago befriended. In her determination to find Rosanne, Helen discovers a shocking American eugenics program—and learns that that while the war had been won in Europe, there are still terrifying battles to be fought at home.